ANALISIS DAN PENINGKATAN PERFORMA WEBSITE COMFYLEARN MENGGUNAKAN STRESS TOOLS - SIAWANG, GABRIELLA; Thayf, Mohammad Sofyan S.; Muawwal, Ahyar (KHARISMA Tech, 2025)
The ComfyLearn website is a supporting platform for educational applications for children aged 3–6 years old that provides information and application downloads. The initial performance audit showed low scores, namely Lighthouse at 42%, PageSpeed 72%, Pingdom 78%, and GTmetrix 80%. This study aims to analyze and improve the performance of the ComfyLearn website using four stress tools: Lighthouse, PageSpeed Insights, Pingdom, and GTmetrix. The research method includes initial analysis, implementation of improvements based on Lighthouse recommendations, and evaluation of the results of the improvements. Data was collected quantitatively through real-time audits of each tool. Improvements focused on five main variables: FCP, LCP, TBT, CLS, and SI. The final results showed a significant performance improvement with a Lighthouse score reaching 99, GTmetrix 93, Pingdom 84, and PageSpeed 79.